The Unique IR2 Protein of Equine Herpesvirus 1 Negatively Regulates Viral Gene Expression - Kim, Seong K. (American Society for Microbiology, 2006)
The IR2 protein (IR2P) is a truncated form of the immediate-early protein (IEP) lacking the essential acidic transcriptional activation domain (TAD) and serine-rich tract and yet retaining binding domains for DNA and TFIIB and nuclear localization signal (NLS). Analysis of the IR2 promoter indicated that the IR2 promoter was upregulated by the EICP0P. The IR2P was first detected in the nucleus at 5 h postinfection in equine herpesvirus 1 (EHV-1)-infected HeLa and equine NBL6 cells. Transient-transfection assays revealed that (i) the IR2P by itself downregulated EHV-1 early promoters (EICP0, TK, EICP22, and EICP27) in a dose-dependent manner; (ii) the IR2P abrogated the IEP and the EICP27P (UL5) mediated transactivation of viral promoters in a dose-dependent manner; and (iii) the IR2P, like the IEP itself, also downregulated the IE promoter, indicating that the IEP TAD is not necessary to downregulate the IE promoter. In vitro interaction assays revealed that the IR2P interacts with TATA box-binding protein (TBP). The essential domain(s) of the IR2P that mediate negative regulation were mapped to amino acid residues 1 to 706, indicating that the DNA-binding domain and the NLS of the IR2P may be important for the downregulation. In transient-transfection and virus growth assays, the IR2P reduced EHV-1 production by 23-fold compared to virus titers achieved in cells transfected with the empty vector. Overall, these studies suggest that the IR2P downregulates viral gene expression by acting as a dominant-negative protein that blocks IEP-binding to viral promoters and/or squelching the limited supplies of TFIIB and TBP.